Impact of human activities on the propagation dynamics from meteorological to hydrological drought in the Nenjiang River Basin, Northeast China - Xubo Geng; Xiaoping Lei; Xiaoyan Song; Junyao Zhang; Wenbin Liu (Journal of Hydrology: Regional Studies)
Study region: Nenjiang River Basin, Northeast China Study focus: Understanding the propagation processes between different types of droughts is crucial for drought early warning and adaptation strategies. Yet, the dynamic effects of human activities on drought propagation remain largely unexplored. Here we assess seasonal dynamic influences of human activities on the propagation of meteorological droughts to hydrological droughts using the Soil and Water Assessment Tool (SWAT) and Copula functions in the Nenjiang River basin, Northeast China. New hydrological insights for the region: Human activities have different effects on drought propagation in different periods and show seasonal characteristics, with effects more pronounced from December to June compared to July to November. The influence peaks in May and June, extending the drought propagation time by 7 to 8 months under moderate meteorological drought conditions. However, human activity's impact diminishes as meteorological drought intensifies. Analysis of historical data (1962-2021) indicates a trend of shortened drought propagation time from July to November, potentially increasing drought risk. Furthermore, human activities tend to reduce the frequency of hydrological droughts but increase their duration and severity, while weakening the correlation between meteorological and hydrological droughts, thereby lowering the propagation probability. This study advances our understanding of human impacts on drought propagation and informs effective water resource management during drought conditions.